A bibliometric profile of optogenetics: quantitative and qualitative analyses - Zhou, Zhonghan; Wang, Xuesheng; Li, Xunhua; Liao, Limin (Frontiers in Neuroscience, 2023)
Introduction Optogenetics is a rapidly developing field combining optics and genetics, with promising applications in neuroscience and beyond. However, there is currently a lack of bibliometric analyses examining publications in this area. Method Publications on optogenetics were gathered from the Web of Science Core Collection Database. A quantitative analysis was conducted to gain insights into the annual scientific output, and distribution of authors, journals, subject categories, countries, and institutions. Additionally, qualitative analysis, such as co-occurrence network analysis, thematic analysis, and theme evolution, were performed to identify the main areas and trends of optogenetics articles. Results A total of 6,824 publications were included for analysis. The number of articles has rapidly grown since 2010, with an annual growth rate of 52.82%. Deisseroth K, Boyden ES, and Hegemann P were the most prolific contributors to the field. The United States contributed the most articles (3,051 articles), followed by China (623 articles). A majority of optogenetics-related articles are published in high-quality journals, including NATURE, SCIENCE, and CELL. These articles mainly belong to four subjects: neurosciences, biochemistry and molecular biology, neuroimaging, and materials science. Co-occurrence keyword network analysis identified three clusters: optogenetic components and techniques, optogenetics and neural circuitry, optogenetics and disease. Conclusion The results suggest that optogenetics research is flourishing, focusing on optogenetic techniques and their applications in neural circuitry exploration and disease intervention. Optogenetics is expected to remain a hot topic in various fields in the future.